2005
DOI: 10.3732/ajb.92.9.1503
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of self‐compatibility in geographically peripheral populations of Leavenworthia alabamica (Brassicaceae)

Abstract: Self-compatibility and adaptations to self-fertilization are often found in plant populations at the periphery of species' ranges or on islands. Self-compatibility may predominate in these environments because it provides reproductive assurance when pollinators or availability of mates limits seed production. This possibility was studied in Leavenworthia alabamica, a flowering plant endemic to the southeastern United States. Populations at the center of the species' range retain sporophytic self-incompatibilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
169
1
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(181 citation statements)
references
References 88 publications
10
169
1
1
Order By: Relevance
“…Self-incompatibility in Solanum recurrent pattern has been the loss of SI on islands or along the edges of species ranges (Rick, 1986;Busch, 2005). This may be at least partially due to pollen limitation in these areas, where the evolution of SC provides reproductive assurance; smaller population size and greater geographical isolation within peripheries also likely contribute to this process (Schoen and Busch, 2008).…”
Section: Js Miller and Jl Kostyunmentioning
confidence: 99%
See 1 more Smart Citation
“…Self-incompatibility in Solanum recurrent pattern has been the loss of SI on islands or along the edges of species ranges (Rick, 1986;Busch, 2005). This may be at least partially due to pollen limitation in these areas, where the evolution of SC provides reproductive assurance; smaller population size and greater geographical isolation within peripheries also likely contribute to this process (Schoen and Busch, 2008).…”
Section: Js Miller and Jl Kostyunmentioning
confidence: 99%
“…Indeed, the evolution of self-compatibility (SC) is considered one of the most common transitions in angiosperm evolutionary biology (Stebbins, 1974), and many examples of multiple transitions within plant lineages have been documented Schoen et al, 1997;Goodwillie, 1999;Igic et al, 2004Igic et al, , 2006. The evolutionary transition from outcrossing to selfing at species range limits (or on oceanic islands) is a recurrent pattern among unrelated lineages of plants (Busch, 2005;Crawford et al, 2008 and references below). Both SI and SC populations have been described for several species of wild tomatoes (Solanum section Lycopersicon), and the presence of SC is often associated with populations located at species range limits (Rick, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…In L. alabamica, two self-compatible races have evolved independently from selfincompatible, outcrossing populations in different parts of the periphery of the species' range, and are characterized by significantly smaller populations, often of lower density [38]. Molecular data have been interpreted as suggesting that a bottleneck could have facilitated the evolution of selfing by reproductive assurance in one race, but not in the other [29], although a study of pollen limitation found no evidence that it has played a role in the evolution of self-compatibility [38]. By contrast, field experiments on pollen limitation in Clarkia xantiana provided evidence for the evolution of selfing by reproductive assurance in populations of small size or low density due to few mates and effective pollinators [39].…”
Section: Ecological and Demographic Contextmentioning
confidence: 99%
“…Second, selfing can be advantageous if it provides reproductive assurance (i.e., when pollinators are scarce or unreliable or when there are few S-alleles in the population) when seed set is limited by the availability of cross pollen (e.g., 1 Stebbins 1957;Baker 1965;Lloyd 1992;Lloyd and Schoen 1992;Schoen et al 1996). This is particularly important for weeds (Baker 1965) and other successional species (Burd 1994;Busch 2005), which typically undergo repeated colonization and local extinction events and whose population sizes are often small.…”
mentioning
confidence: 99%